Infection Rate Comparison during Transition from Hospital to Office WALANT Enabled by Virtual Reality - Tannur C. Oakes, MD; Karren C. Wong, MD; Kyle J. Schank, MD; Pam Haan, BSN; Stephanie M. Bray, MD, MS; James H. W. Clarkson, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. We transitioned our hand practice from the operating room (OR) to our office-based procedure room (OPR) to offer wide-awake, local anesthesia, no tourniquet (WALANT). We have established that using wide-awake virtual reality improves patient comfort and anxiety during wide-awake procedures and helps facilitate our patients’ choice of venue. We aimed to assess the effect of this transition on infection rates for procedures performed by a single surgeon in the OR versus the OPR. Methods:. A retrospective chart review was performed on a single surgeon’s adult patients who underwent elective and closed traumatic upper limb surgeries. A surgical site infection was defined as superficial or deep, based on clinical examination conducted by the surgeon, and was treated with antibiotics within a 4-week postoperative window. Results:. From August 2017 to August 2019, 538 (216 OR and 322 OPR) consecutive cases met inclusion criteria. There were six (2.78%) superficial infections and zero deep space infections in the OR cohort compared with four (1.24%) superficial and zero deep space infections in the OPR cohort with no statistical significance. Two-thirds of cases were converted to WALANT and delivered in the office. Conclusions:. This narrative study concurs with the current literature that WALANT in the office setting is as safe as the hospital OR-based procedures for selected elective cases. By transitioning suitable cases from the OR to the OPR, a surgeon’s overall infection rate should not change.